Legal Discrimination in the United States based on Sexual Orientation and Gender Identity - Miller, Mark C (American Studies in Scandinavia, 2017)
When the U.S. Supreme Court declared that same-sex marriage would be legal throughout the country, that decision did not end the possibility of other types of discrimination on the basis of sexual orientation or gender identity. The U.S. Supreme Court has been very unclear about what standard to use when the courts face claims of discrimination based on these characteristics. In cases decided under the Fourteenth Amendment’s Equal Protection Clause, the Court has stated that lower courts should use one of three standards, based on the type of discrimination alleged. These three standards for review are known as rational basis, intermediate review, and strict scrutiny. This article, based on both empirical and normative analysis, will explore the proper legal standard that the Supreme Court should use in these cases. Since several states have begun to enact laws that encourage discrimination on the basis of sexual orientation and gender identity, this article will argue that the Supreme Court should use strict scrutiny in these cases because the LGBT community is clearly a discrete and insular minority subject to targeted discrimination.